Developing Future Teachers’ Competences in IT and Robotics Using Virtual and Augmented Reality: A Study of Teaching Effectiveness - Uderbayeva, Nurgul; Karelkhan, Nursaule; Zharlykassov, Bakhtiyar; Radchenko, Tatyana; Imanova, Aliya (Journal of Technical Education and Training, 2025)
The research addresses the need for innovative learning methods to develop competencies in future specialists, driven by rapid digitalization and globalization of social relations. The work aims to study the technologies of virtual (VR) and augmented reality (AR) in the context of developing the information and communication competencies of future teachers. Logical analysis, functional analysis, abstraction, deduction, and induction were utilized. The objects of the study were characterized, their key features were determined, and their role in the formation and development of information and communication competencies was identified. It was noted that using VR and AR technologies in the modern digital age is crucial for enhancing information literacy, communication competence, and motivation in the learning process. During the experiment, which involved senior students, namely 81 students from Kostanay Engineering and Economics University named after M. Dulatov and 60 students from U. Sultangazin Pedagogical Institute, Akhmet Baitursynuly Kostanay Regional University, a program using VR and AR technologies was developed and implemented. It was found that the level of communication competencies at the optimal indicator increased by 40%, and the learning efficiency increased by 31%. The study highlights the importance of structured training in enhancing communication competence and digital readiness among future educators in Kazakhstan. It suggests that teachers need to develop digital competencies, especially in using VR and AR technologies, to adapt to modern educational demands. This research enhances teacher education by equipping educators with essential digital skills for effective teaching.